White M. T., Read M. G., Sayma A. I. Comparison between single and cascaded organic Rankine cycle systems accounting for the effects of expansion volume ratio on expander performance / trans. from Engl. M. A. Fedorova - M. A. Fedorova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Compared to single-stage organic Rankine cycle (ORC) systems, cascaded ORC systems, in which a high-temperature topping cycle and low-temperature bottoming cycle are coupled together, could have advantages in terms of removing the potential for sub-atmospheric condensation conditions and improving expander performance as the expansion process is effectively divided across two stages. Moreover, reducing the expansion volume ratio could facilitate the use of volumetric expanders, such as twin-screw expanders, which, in turn, could facilitate two-phase expansion to be utilised in one, or both, of the cycles. The aim of this paper is to compare single-stage and cascaded ORC systems, accounting for the effect of the expander volume ratio on expander performance. To investigate this, thermodynamic models for single-stage and cascaded ORC systems are developed, which include variable efficiency expander models for both radial turbines and twin-screw expanders that can estimate the effect of the expansion volume ratio on the expander isentropic efficiency. Using this model, three different scenarios are compared for different temperature heat-source temperatures, namely: (i) single-stage ORC systems with vapour-phase expansion obtained using a turboexpander; (ii) single-stage ORC systems operating with a twin-screw expander, with the possibility for two-phase expansion; and (iii) cascaded cycles with either vapour- or two-phase expansion. The results from this comparison are used to identify applications where cascaded ORC systems could offer performance benefits